Determination of heavy metal elements concentration in soils and tailing sediments from lateritic nickel post-mining areas in Motui District, Southeast Sulawesi - Muhardi Mustafa; Adi Maulana; Ulva Ria Irfan; Adi Tonggiroh (Journal of Degraded and Mining Lands Management, 2022)
Heavy metal elements concentration study has been determined from soils and tailing sediments in laterite nickel post-mining area in Motui District Southeast Sulawesi. This study aimed to determine the concentration of some heavy metal elements, especially Fe, Co, Mn and Cr, from surface soils sediments in waste dump sites and tailing sediments in settling ponds from lateritic nickel post-mining areas. A total of 20 samples consisting of 18 soil samples and 2 tailing sediments samples were systematically collected for the study. The soil samples from the waste dump site profile were collected from 3 layers which were divided based on the colour of the soils from top to bottom, namely Layer C, Layer D and Layer E. Six soil samples were taken from each layer with space between each sample in one layer was about 50 – 60 cm. The samples were sent to the laboratory and analysed using Atomic Absorption Spectrometer (AAS) method to determine the concentration of heavy elements. Metal-bearing minerals detected from the bedrock consists of chromite, manganese, magnetite and limonite which are responsible for the Cr, Mn and Co, and Fe content, respectively. The result showed that Fe content is significantly higher in soil samples from Layer C and tailing sediments with dark red to brown in colour, suggesting the strong relation between Fe content and colour index. The general element mobility trend showed that Mn and Co are positively correlated in soil sampling from all layers and tailing samples, whereas Fe and Cr show a negative correlation trend in Layer C, D and tailing sediments but positively correlated in Layer E.